What do you know about food chains and food webs? - Slade, Suzanne (New York : PowerKids Press, 2008)
Explores twenty questions about food chains and webs, covering producers and consumers, herbivores, predators, scavengers, and other topics.
Includes index.
3.3
K-3
Keywords: Food chains (Ecology) -- Miscellanea -- Juvenile literature; Food chains (Ecology); Food chains (Ecology); Food chains (Ecology)